University Students’ Perceptions of a 30-Minute Break During Class: A Realistic Practice for Wellness? - Kell, Shannon (Teaching and Learning Inquiry, 2024)
This SoTL study aimed to discover how teacher education students engaged with a 30-minute unstructured break during a weekly three-hour lecture. Cognitive fatigue and resulting stress accumulation have negative effects on wellness. Education students can accumulate significant stress when studying and preparing. This, in turn, affects their career outlook and may affect teacher retention. Pausing a cognitively demanding task and taking a break can reverse the strain reaction and support sustainable, long-term wellness. However, taking an effective break is often difficult because it can be perceived as a waste of time and a loss of productivity. Research shows the opposite effect. If we educate higher education students about the benefits of taking effective breaks and then model this practice in class, can we promote an accessible and realistic stress management strategy? Can student teachers potentially take this strategy with them into their teaching careers and classrooms? Using pre- and post-surveys as well as “Weekly Break Logs” during class (N = 70), followed by a post-course focus group (n = 4), the study found that 100% of participants post-course valued the break. They spent it socializing or going for short walks and did not spend it on their devices. The majority felt refreshed and motivated to return to learning following the break. Focus group findings revealed the value of taking breaks, and participants were motivated to continue this practice in their professional lives. Read the corresponding ISSOTL blog post here.